The hydraulic resistance in the small-scale pillow-plate heat exchangers - Arsenyeva, O. P. (Національний університет "Львівська політехніка", 2019)
The Pillow-Plate Heat Exchangers (PPHEs) are rated as innovative type of heat transfer equipment. The present paper gives the information about the research made in Paderborn University aimed to investigate the heat transfer and pressure drop in the channels of the small-scale PPHE.
Keywords: heat exchangers; pillow plates; heat transfer; heat exchanger design; hydraulic resistance